Implementation of Performance Appraisal for Islamic Bank in Indonesia Using CAMELS Method - Sodiq, Ahmad; Ratnasari, Ririn Tri; Mawardi, Imron; Pitchay, Anwar Allah (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
The assessment of Islamic bank performance measured by the CAMELS method through the 2016-2020 CAR analysis as of January shows that the performance of Islamic commercial banks from year to year shows an increase in the management of Islamic bank management. Where it can be seen that in 2016 to 2020 as of January Islamic commercial banks showed a very healthy condition because they were in the CAR position> 11%. ROA, is used to measure the health of the bank from the income aspect by comparing the net profit achieved with the total assets owned by the bank. The condition of the NPF of Islamic Banks is very healthy as indicated by the small number of bad debts and problematic financing by customers at Islamic banks. Meanwhile, the condition of the LDR of Islamic Banks fluctuates where in 2016 the LDR was in an unhealthy predicate of 85.99%, and in 2017 to January 2020 it was in a very healthy condition because it was in a position of more than 100%. BOPO of Islamic general banks showed unhealthy conditions in 2016, then experienced a significant increase in 2017 in healthy conditions and in 2018 until January 2020 in very healthy conditions.